Feeding habits of longnosed skate, Dipturus oxyrinchus in the Sardinian seas (central-western Mediterranean). - MULAS, ANTONELLO; FOLLESA, MARIA CRISTINA; BELLODI, ANDREA; CANNAS, RITA; Cau Al; MARONGIU, MARTINA FRANCESCA; PORCU, CRISTINA; Cau A. (2012)
The feeding habits of longnosed skate, Dipturus oxyrinchus, in the Sardinian seas (central-western Mediterranean) were analysed with respect to fish size and depth. A total of 254 stomachs (%Cv = 5.12) were collected from specimens, 93 to 1153 mm TL, caught at depths between 121 and 671 m during experimental trawl surveys in the period 2005-2010. The 75 prey items found belonged to five major taxa: Crustacea, Osteichthyes, Chondrichthyes, Mollusca and Polychaeta. Levin’s index value (Bi = 0.35) showed a narrow niche breadth. Crustaceans (%IRItot = 81.32), particularly Decapods, Mysids and Euphasiids, were the most important preys. Molluscs (%IRItot = 14.97), mainly Cephalopods, were second, replacing Crustaceans among individuals > 750 mm TL. Trophic level was 3.77 (s.e. = 0.47). During growth a narrowing of niche breadth and an increasing of trophic level were observed (Bi = 0.24, 0.15, 0.65 and TROPH = 3.56 ± 0.57, 4.19 ± 0.77, 4.36 ± 0.79 for immature, subadults and adults, respectively). Immatures (139 individuals)feed mainly on Mysids, and particularly on Lophogaster typicus (%IRI = 63.14), replaced by Euphasiids, mainly Meganyctiphanes norvegica (%IRI = 55.5), among subadults. Crustaceans began less important among adults, being replaced by Cephalopods (%IRItot = 46.74). These feeding patterns ensured low intraspecific competition levels. Differences in the diets with depth were noticed, mainly attributable to the particular bathymetric distribution of the species. Cephalopods were the main prey items in the lower stratum (<200 m), replaced by Crustaceans in the deeper bathymetric strata (200-500 and > 500 m).